2008
DOI: 10.1021/jm070549+
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Small-Molecule Solvation Free Energies: An Informal Blind Test for Computational Chemistry

Abstract: Experimental data on the transfer of small molecules between vacuum and water are relatively sparse. This makes it difficult to assess whether computational methods are truly predictive of this important quantity or merely good at explaining what has been seen. To explore this, a prospective test was performed of two different methods for estimating solvation free energies: an implicit solvent approach based on the Poisson-Boltzmann equation and an explicit solvent approach using alchemical free energy calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
447
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(466 citation statements)
references
References 69 publications
17
447
2
Order By: Relevance
“…However, predominantly the latter approach was used—experimental measurements were determined by combining both experimental values for aqueous hydration free energies and partition coefficients measured between water and nonaqueous liquids 40. The average uncertainty in experimental values of solvation free energies reported by the authors of the Minnesota solvation database is ∼ 0.2 kcal mol −1 for the subset used in this study 40, 68, 69. However, this uncertainty is likely to be non‐normally distributed amongst the members of the database, such that individual molecules may have larger or smaller errors in their experimental Δ G estimates.…”
Section: Resultsmentioning
confidence: 99%
“…However, predominantly the latter approach was used—experimental measurements were determined by combining both experimental values for aqueous hydration free energies and partition coefficients measured between water and nonaqueous liquids 40. The average uncertainty in experimental values of solvation free energies reported by the authors of the Minnesota solvation database is ∼ 0.2 kcal mol −1 for the subset used in this study 40, 68, 69. However, this uncertainty is likely to be non‐normally distributed amongst the members of the database, such that individual molecules may have larger or smaller errors in their experimental Δ G estimates.…”
Section: Resultsmentioning
confidence: 99%
“…61 For our test set, we took as a starting point the experimental data compiled by Rizzo et al 19 and removed the charged molecules. In an attempt to construct a set of all neutral compounds with known hydration free energies, we added (neutral) amino acid side chain analogues and other compounds from our previous studies in explicit solvent, 22,35 and various small molecules from another set of 52 small molecules and associated references provided by J. Peter Guthrie, 41 removing redundancies. The result is a set containing 504 neutral small molecules.…”
Section: B Test Set Selectionmentioning
confidence: 99%
“…The root mean square error (RMSE) of the computation results is 1.77 kcal/mol and the average error is 1.42 kcal/mol. In comparison, Nicholls et al [39] reported a RMSE of 1.87 kcal/mol for the same set of molecules by the linear Poisson model and further, the RMSE was reduced to 1.71 ± 0.05 kcal/mol [39] by their explicit solvent approach, which is much more expensive. Additionally, the RMSE in the current work is only slightly greater than the one (RSME=1.76 kcal/mol) reported in [18], where the biomolecular surface is defined and generated from a nonlinear mean curvature flow equation so extra computational efforts are necessary.…”
Section: Applicationsmentioning
confidence: 99%